Identifying Frequency of Dementia in Parkinson's Disease (Medical Forum Monthly, 2021)
Objective: The objective of the study was to determine the frequency and characteristics of dementia in Parkinson’s disease.Study Design: A descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Liaquat College of Medicine & Dentistry and Neuro Clinic & Falij Care, Karachi from October 2018 to March 2019.Materials and Methods: This study was conducted on 35 patients presenting with memory impairment at the obtaining ethical approval from IRB-Liaquat College of Medicine and Dentistry. Adult patients of more than 18 years of age presenting with multiple cognitive deficits with a score of 23 or less out of 30 on Folstein mini-mental state examination were included in the study. The results were tabulated and analyzed using SPSS-21.Results: A sample of 35 cases (23 males and 12 females) with PD was included. The mean age of patients was 57.4 ± 13.9 years and range between 40-85 years. Out of 35 cases six (17.1%) had PD with dementia (PDD); while 29 (82.85%) out of 35 were non-demented. Out of six demented patient's five (83%) were males and one (17%) was female. The average values of outcome of different variables were: Time Orientation 3.1 ± 1.8 , Registration 1.7 ± 1.3, Attention and Calculation 1.4 ± 1.7, Recall 1.4 ± 1.4, and Language 4.5 ± 3.2. The average score of Mini Mental Score Examination was 15.3 ± 10.36.Conclusion: In conclusion, this study revealed that the frequency of developing dementia in PD was less than one third in study sample.